Analysis of the Implementation of Environmental Costs in a Case Study at the Banjarmasin Islamic Hospital - Fatmawati Bakri Noor; Hj. Ade Adriani; Norlena; Riyadi, Padlah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to uncover waste management activities and environmental costs of environmental cost reporting at the Islamic Hospital of Banjarmasin. This researcher uses a qualitative paradigm with a case study design. The research scope is the Unit of Environmental Health Sanitation with the accounting process of environmental management, hospital waste management's data focus, and expenditures for waste costs. Primary data were collected through in-depth interviews and observations; secondary data, through documentation. The results revealed that environmental management accounting systems in 2019 and 2020 found hidden environmental costs from waste management cost reports in the Financial Statements. For example, the environmental cost report applied to the SKL Unit revealed Rp 677.646.500 and Rp 459.521.600 not presented as an environmental cost in 2019 and 2020. The implementation of environmental cost accounting through environmental cost reporting at the Islamic Hospital of Banjarmasin revealed that special reports in environmental management accounting could be used as information by the management of the Islamic Hospital of Banjarmasin in planning and controlling environmental responsibility activities